Ambivalências éticas do Anonymous Brasil: discursos políticos sobre liberdade e o Marco Civil da Internet - Moraes, André de Nardi Senna (2016)
This work aims to reflect upon the Anonymous net-activist and hacktivist moral identities in Brazil. It raises questions about how such identities can illustrate discourse disputes in the network politics environment. Our objective is to discuss the relations between Anonymous Brazil s hacker ethics and its political positions about freedom on the internet. The Anonymous are an idea, a collective of members, inspired by the archetypes of the hacker community to claim certain ideals of civilian rights, such as freedom of expression, free file sharing and the right to privacy. Similar to the political interactions in human nature, the relationship between Anonymous and the institutions they consider abusive are asymmetric and based on manifestations of power and counter power. To configure such relationship, this dissertation dedicates to contextualize power in human interactions, the formulation of a hacker subculture as an expression of resistance and how the ethical principal of these elements help to guide an Anonymous ideal of subversion. By means of critical discourse analysis, this work shall deconstruct Anonymous speeches about the Brazilian Civil Rights Framework for the Internet. By such approach, this investigation identifies traces of moral ambivalences that unsteadily navigate between notions of collectivism and individualism, creation and destruction, freedom and regulation.